The effect of blood transfusion on central venous oxygen saturation in critically ill patients admitted to a neurointensive care unit. Issue 5 (1st August 2016) - Surve, R. M.; Muthuchellappan, R.; Rao, G.S.U.; Philip, M.
SUMMARY: Background: Literature suggests poorer outcomes during anaemia as well as following red blood cell transfusion (BT) in brain injured patients. Recently, central venous oxygen saturation (ScvO2 ) has been proposed as a physiological trigger to guide red BT. In this study, we looked at ScvO2 changes following BT in patients admitted to a neurointensive care unit (NICU). Study design: In this prospective, observational study, adult, acutely ill neurological patients of >18 years were recruited. The following parameters were measured before and immediately after transfusion and then at 6, 12, 18 and 24 h after transfusion: haemoglobin (Hb), ScvO2 and central venous oxygen partial pressure (PcvO2 ) (blood sampled from central venous catheter). Simultaneously, hemodynamic parameters [central venous pressure (CVP), heart rate (HR), mean arterial pressure (MAP) and systolic blood pressure (SBP)] were also noted. Results: Data from 70 adult patients were analysed. Following BT, significant improvement was noted in Hb, ScvO2 and all hemodynamic parameters. The ScvO2 changes correlated significantly with the number of units of BT ( P  = 0·039), pre‐transfusion Hb ( P  = 0·010), ScvO2 ( P  = 0·001) and PcvO2 ( P  = 0·001). When receiver operating characteristic (ROC) curves were drawn, optimum cut‐off values of baseline ScvO2 and Hb to predict the need for transfusion in terms of oxygen delivery were 70% and 8·6 gm dL −1 respectively. Discussion: Baseline ScvO2 <70% appears to be a useful physiological trigger for deciding the need for BT in brain injured patients. Whether improvement in ScvO2 leads to improvement in regional brain oxygenation needs to be studied.